Roughness Variation Impact on the Morphological Evolution at the Medjerda River: Telemac 2D-Sisyphe Modeling - Hammami Saber; Romdhane Hela; Soualmia Amel; Kourta Azeddine (Environment and Natural Resources Journal)
Sediment transport plays a vital role in river management and flood protection, particularly in regions prone to erosion and deposition. The study aims to assess the impact of roughness modification on the sediment transport process in the Medjerda, Tunisia’s longest perennial river, following a decade of dredging activities implemented for flood protection measures in the Boussalem city. We used the Telemac Sisyphe model to stimulate sediment 17.8 km section, which regularly undergoes dredging crossing the city of Boussalem. This section contains two distinct parts: first a smooth riverbed followed by the variable roughness on both sides of the banks, which is influenced by the existing vegetation cover. The study developed four simulation scenarios, with a smooth riverbed maintained in call cases while the roughness of the second part increasing from smooth to rough. The model-generated outputs facilitated a comprehensive longitudinal and transverse comparative analysis, focusing on flow velocity, shear stress, and bed evolution profile in response to varying roughness levels. The results show a reduction in erosion and deposition phenomena as the roughness as the bank’s roughness increases. this the crucial role of vegetation in stabilizing river banks by, strengthening the cohesion of the riverbed, thus minimizing erosion risks and excessive sediment transport, ultimately maintaining the riverbed’s integrity. These findings contribute to understanding of sedimentation patterns in the Medjerda River and facilitated the prediction of potential impacts on its fluvial morphology.